Gothic literature a Gale critical companion - Bomarito, Jessica 1975-.; Gale Group (Detroit Thomson/Gale, 2006)
Spans all facets of gothic literature, including visual and performing arts, society and culture, themes, and settings. Includes primary source documents and critical material to provide a contextual perspective, a related chronology of key events, full-text commentaries, and lists of further readings.
v. 1. Topics -- v. 2. Authors A-K -- v. 3. Authors L-Z.
Electronic reproduction.
Keywords: English literature -- History and criticism -- Handbooks, manuals, etc; Gothic revival (Literature) -- Great Britain -- Handbooks, manuals, etc; Gothic revival (Literature) -- United States -- Handbooks, manuals, etc; Horror tales, American -- History and criticism -- Handbooks, manuals, etc; Horror tales, English -- History and criticism -- Handbooks, manuals, etc; American literature -- History and criticism -- Handbooks, manuals, etc; Electronic books